2017
DOI: 10.1021/acs.bioconjchem.7b00013
|View full text |Cite
|
Sign up to set email alerts
|

Improved Lysosomal Trafficking Can Modulate the Potency of Antibody Drug Conjugates

Abstract: Antibody drug conjugates (ADCs) provide an efficacious and relatively safe means by which chemotherapeutic agents can be specifically targeted to cancer cells. In addition to the selection of antibody targets, ADCs offer a modular design that allows selection of ADC characteristics through the choice of linker chemistries, toxins, and conjugation sites. Many studies have indicated that release of toxins bound to antibodies via noncleavable linker chemistries relies on the internalization and intracellular traf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 64 publications
0
26
0
1
Order By: Relevance
“…There are a few recent reports of bispecific ADC with the internalizing arm binding to either a lysosomal protein or an antigen that rapidly traffics to the lysosome (5)(6)(7). In most cases, the observation is empirical and the bispecific effect is rather moderate, suggesting that key parameters affecting bispecific-induced internalization have not been fully delineated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are a few recent reports of bispecific ADC with the internalizing arm binding to either a lysosomal protein or an antigen that rapidly traffics to the lysosome (5)(6)(7). In most cases, the observation is empirical and the bispecific effect is rather moderate, suggesting that key parameters affecting bispecific-induced internalization have not been fully delineated.…”
Section: Discussionmentioning
confidence: 99%
“…For example, through the biparatopic design and the consequent cross-linking effect, HER2 antigen has been targeted for improved ADC internalization (4). In another example, a bispecific composed of a moderately internalizing antibody arm (anti-HER2) and an internalization-inducing antibody arm (anti-CD63, anti-PRLR, or anti-APLP2) was constructed and used to improve ADC uptake (5)(6)(7). However, despite those efforts, the bispecific ADC only showed limited improvement over the parental monospecific anti-HER2 ADC, suggesting that key parameters regarding this design remains to be delineated.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, research had demonstrated that ADCs with a payload conjugated to the light chain of the mAb were shown to perform significantly higher in vivo efficacy compared with those conjugated to the heavy chain (Shen et al ., ). On the other hand, noncleavable linkers are intended to be more stable in the bloodstream and extracellular space, because ADCs release their toxins relying on the internalization and lysosomal degradation (DeVay et al ., ; Peters and Brown, ; Ritchie et al ., ). Therefore, ADC efficacy depends in part on antibody–antigen interaction at the cell surface triggering the internalization and lysosomal trafficking.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, whilst demonstrating the potential of such a "drag and degradation" approach, DeVay et al noted limitations to this strategy [36]. A model bispecific ADC with a HER2 arm and an Amyloid Precursor Like Protein 2 (APLP2) arm was prepared.…”
Section: Endocytosis and Lysosomal Traffickingmentioning
confidence: 99%